2019
DOI: 10.1002/macp.201800536
|View full text |Cite
|
Sign up to set email alerts
|

Porous Polymers Derived from Octavinylsilsesquioxane by Cationic Polymerization

Abstract: A new rapid and efficient approach is developed for the preparation of porous materials via cationic polymerization of octavinylsilsesquioxane (OVS). The reaction proceeds rapidly and efficiently at room temperature, forming a predominantly covalent porous network polymer. A series of experiments are conducted to clarify the effects of reaction time, temperature, and solvent on the polymerization process. The results show that all the products possess a nanoporous structure with surface areas of approximately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…It is shown that the PTVPP holds a carbon dioxide adsorption capability as high as 13.3 wt% at 273 K and 8.2 wt% at 298 K. These values are slightly higher than that of PTVP‐1 which are 12.3 and 6.8 wt% at 273 and 298 K, respectively (Figure a). These performances are also superior to the recent reports . The higher results can be attributed to the existence of nitrogen element in PTVPP backbone which shows better affinity of carbon dioxide .…”
Section: Methodsmentioning
confidence: 51%
See 3 more Smart Citations
“…It is shown that the PTVPP holds a carbon dioxide adsorption capability as high as 13.3 wt% at 273 K and 8.2 wt% at 298 K. These values are slightly higher than that of PTVP‐1 which are 12.3 and 6.8 wt% at 273 and 298 K, respectively (Figure a). These performances are also superior to the recent reports . The higher results can be attributed to the existence of nitrogen element in PTVPP backbone which shows better affinity of carbon dioxide .…”
Section: Methodsmentioning
confidence: 51%
“…It would be more ideal to develop new synthetic methods of POPs with higher surface areas and much milder conditions. Liu and co‐workers have reported an interesting cationic polymerization of porous polymers based on non‐aromatic vinyl monomers, which successfully achieved a series of porous polymers with moderate surface area for gas adsorption . However, it is still challenging to synthesize POPs with high surface areas under very mild conditions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, only a high cross-linking degree was suitable to generate a porous polymer. Currently, the synthesis and application of nanoporous organic polymers and their composites remain areas of intense research activity [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Nevertheless, hard templating strategies appeared to be a suitable pathway to generate nanostructured polymeric materials and soft materials in general [24].…”
Section: Introductionmentioning
confidence: 99%